2020
DOI: 10.1039/c9nr09625f
|View full text |Cite
|
Sign up to set email alerts
|

Sub-100 nm 2D nanopatterning on a large scale by ultrafast laser energy regulation

Abstract: Coupling ultrafast light irradiation to surface nanoreliefs leads to periodic patterns, achieving record processing scales down to tens of nanometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Other substantial parameters are the polarization angle between the two delayed pulses, number of pulses, pulse duration and initial surface roughness. Based on previous experiments, the chosen number of double-pulse sequences (N DPS ) was 25 pulses [25]. A cross-polarized ultrashort double pulses are applied in order to break the surface isotropy, avoiding the formation of LIPSS.…”
Section: Advanced Surface Topography Control As a Function Of Time Delay And Laser Fluencementioning
confidence: 99%
See 1 more Smart Citation
“…Other substantial parameters are the polarization angle between the two delayed pulses, number of pulses, pulse duration and initial surface roughness. Based on previous experiments, the chosen number of double-pulse sequences (N DPS ) was 25 pulses [25]. A cross-polarized ultrashort double pulses are applied in order to break the surface isotropy, avoiding the formation of LIPSS.…”
Section: Advanced Surface Topography Control As a Function Of Time Delay And Laser Fluencementioning
confidence: 99%
“…Driven by near-field light enhancement, periodic patterns recently approached ultimate scales down to tens of nanometers [25]. A self-organization of unusual arrays of nanocavities of 20 nm diameter with a periodicity down to 60 nm was created on a Nickel surface oriented in (100) plan.…”
Section: Introductionmentioning
confidence: 99%
“…Pushing more the coupling between radiation and landscape, further record sizes can be demonstrated. Abou-Saleh et al [101] have indicated using double pulse sequences the emergence of other types of 2D high-resolution patterns (notably hexagonal), where the regulation concept comes from combining crossedpolarization and time-delay for irradiations close to the modification threshold. This particular parameter range promotes geometry complexity and, notably, structural size well below 100 nm.…”
Section: Focal Engineering and Near-field Processing: Sub-wavelength mentioning
confidence: 99%
“…A cavity is formed, surrounded by denser regions, with a dimension Reprinted with permission from a study by Nathala et al [23] ©Springer-Nature. (c) Nanohole pattern on single crystal surfaces irradiated with double pulse sequences with polarization control [101].…”
Section: Focal Engineering and Near-field Processing: Sub-wavelength mentioning
confidence: 99%
See 1 more Smart Citation